Prevalence of dementia subtypes in a developing country: a clinicopathological study (Clinics, 2013)
OBJECTIVES: To assess the distribution of dementia subtypes in Brazil using a population-based clinicopathological study. METHOD: Brains from deceased individuals aged ≥50 years old were collected after the next of kin signed an informed consent form and provided information through standardized questionnaires. Post-mortem clinical diagnoses were established in consensus meetings, and only cases with moderate or severe dementia or without cognitive impairment were included in the analysis. Immunohistochemical neuropathological examinations were performed following the universally accepted guidelines. A diagnosis of Alzheimer's disease was made when there were at least both a moderate density of neuritic plaques (Consortium to Establish a Register for Alzheimer's disease B or C) and Braak stage III for neurofibrillary tangle distribution. For the diagnosis of vascular dementia, at least three zones or strategic areas had to be affected by infarcts, lacunae, or microinfarcts. RESULTS: From 1,291 subjects, 113 cases were classified as having moderate or severe dementia, and 972 cases were free of cognitive impairment. The neuropathological diagnoses of the dementia sub-group were Alzheimer's disease (35.4%), vascular dementia (21.2%), Alzheimer's disease plus vascular dementia (13.3%), and other causes of dementia (30.1%). Small-vessel disease, which alone was not considered sufficient for a vascular dementia diagnosis, was present in 38.9% of all of the dementia cases and in 16.8% of the group without cognitive impairment (odds ratio = 2.91; 95% confidence interval, 1.53-5.51), adjusted for age, sex, and education. CONCLUSIONS: The relatively high frequencies of vascular dementia and small-vessel disease in the dementia sub-group constitute relevant findings for public health initiatives because control of vascular risk factors could decrease the prevalence of dementia in developing countries.